Optimisation of enzymatic hydrolysis for concentration of vitamin E in palm fatty acid distillate - Chu, B.S.; Quek, S.Y.; Baharin, B.S. (Elsevier Science, 2003)
Vitamin E was concentrated from palm fatty acid distillate (PFAD) in this study using a commercial immobilised Candida antarctica lipase (Novozyme 435). The PFAD and water mixture was hydrolysed at 65±1°C. Free fatty acids (FFA) liberated were neutralised using an alkali and the salts formed were then washed off. Factors affecting the enzymatic hydrolysis and vitamin E concentration of extracted fraction were optimised using response surface methodology (RSM). A central composite design was employed to study the responses, namely percentage of FFA (Y1) and vitamin E concentration (Y2), while lipase concentration (X1), reaction time (X2) and water content of the reactant (X3) were the independent variables. Results showed that the regression models generated adequately explained the data variation and significantly represented the actual relationships between the reaction parameters and the responses. For both regression models of FFA and vitamin E, the first- and second-order variable of water content was the most significant factor. The optimum reaction parameters for maximum yield in FFA and vitamin E concentrations were identified from their respective contour plots. It was suggested that for maximum vitamin E concentration, the hydrolysis should be carried out with 2.5% (w/w) of lipase and 45.2-47.3% (v/w) of water for 5.5-5.7 h.